Changes in Self-Rated Physical Health After Moving Into Permanent Supportive Housing. Issue 7 (September 2019) - Rhoades, Harmony; Wenzel, Suzanne L.; Henwood, Benjamin F.
Purpose: Homelessness is associated with poor health outcomes and heightened risk of premature mortality. Permanent supportive housing (PSH) is a key solution for ending homelessness, but there is insufficient evidence of a relationship between PSH and improvements in physical health. Self-rated health—a consistent predictor of mortality—is a meaningful approach to understanding health improvements in PSH. Design: Longitudinal, observational design with interviews at baseline, 3-months, 6-months, and 12-months (with 91% retention at 12-months). Setting: Permanent supportive housing in Los Angeles, CA. Subjects: Four hundred twenty-one adults moving into PSH (baseline interview prior to/within 5 days of housing). Measures: Three self-rated health assessments: general health status, and limitations to physical and social activity because of health problems. Results: Generalized Estimating Equations (controlling for demographics and important health covariates; n = 420) found self-rated general health status improved between baseline and 3-months (coef: 0.13; 95% confidence interval [CI]: 0.02-0.24) and persisted at 12-months (coef: 0.16; 95% CI: 0.05-0.27). Improvements in limitations to physical or social activity because of health problems started at 6-months posthousing (physical: coef: 0.25; 95% CI: 0.12-0.39; social: coef: 0.18; 95% CI: 0.05-0.32) and persisted through 12-months (physical: coef: 0.14; 95% CI: 0.01-0.27; social: coef: 0.16; 95% CI: 0.02-0.29). Conclusions: Despite limitations associated with observational study design, these findings provide further evidence that PSH may improve health among those with homelessness histories.